2006
DOI: 10.1016/j.jecp.2005.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of discourse context in developing word form representations: A paradoxical relation between reading and learning

Abstract: To acquire representations of printed words, children must attend to the written form of a word and link this form with the word's pronunciation. When words are read in context, they may be read with less attention to these features, and this can lead to poorer word form retention. Two experiments with young children (ages 5-8 years) conWrmed this hypothesis. In our experiments, children attempted to read words they could not previously read, during a self-teaching period, either in context or in isolation. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 17 publications
9
65
3
1
Order By: Relevance
“…This is consistent with previous orthographic learning studies that have manipulated context in a similar way (Ricketts et al, 2008), have made comparisons between exposure in isolation and exposure in context (Nation, Angell, et al, 2007) or have investigated word learning after reading cohesive versus scrambled passages (Cunningham, 2006). However, in some cases reduced orthographic learning has been observed for items learned in context in relation to items learned in isolation (Landi et al, 2006;Stuart, Masterson, & Dixon, 2000). It is worth noting that reading in isolation and reading in context place very different reading and language demands on a child whereas the demands in this study were relatively constant across context conditions.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is consistent with previous orthographic learning studies that have manipulated context in a similar way (Ricketts et al, 2008), have made comparisons between exposure in isolation and exposure in context (Nation, Angell, et al, 2007) or have investigated word learning after reading cohesive versus scrambled passages (Cunningham, 2006). However, in some cases reduced orthographic learning has been observed for items learned in context in relation to items learned in isolation (Landi et al, 2006;Stuart, Masterson, & Dixon, 2000). It is worth noting that reading in isolation and reading in context place very different reading and language demands on a child whereas the demands in this study were relatively constant across context conditions.…”
Section: Discussionsupporting
confidence: 87%
“…Previous research has shown that word reading is supported by context (Archer & Bryant, 2001;Nation & Snowling, 1998). However, context does not appear to facilitate orthographic learning in the self-teaching paradigm; some researchers have found no effect of context (Cunningham, 2006;Nation, Angell, et al, 2007;Ricketts, Bishop, & Nation, 2008) and others have reported reduced orthographic learning for items learned in context in relation to items learned in isolation (Landi, Perfetti, Bolger, Dunlap, & Foorman, 2006;Stuart, Masterson, & Dixon, 2000).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…It is not the case that young children learn to read words by contextual guessing, as is clear from a large evidence base. [49][50][51][52] To the contrary, the foundation of learning to read in English is the alphabetic principle and from this, the development of high quality phonological decoding skill. 1,8,9 This provides the means for orthographic learning-the gradual accumulation of orthographic knowledge, via reading experience.…”
Section: Questions To Ask About the Lexical Legacy Hypothesismentioning
confidence: 99%
“…The present report is an attempt to answer these and related questions in a fairly large sample of 361 Cantonese-speaking students in Hong Kong in secondary 1, 3 and 4 between the ages of 13 and 16 years; and a sub-sample of less skilled language and reading comprehenders compared with a sub-sample of skilled comprhenders in Chinese. In our study we posit as important lexical knowledge in the abstract lexicon, which includes what Landi, Perfetti, Bolger, Dunlap, and Foorman (2006) call ''specific word form representations'' to denote orthographic information and the mapping between orthographic and phonological information. Lexical structure refers to the organization of the components of lexical knowledge to facilitate language and reading comprehension.…”
Section: Introductionmentioning
confidence: 99%